42 South west peninsula quality improvement fellows: mentoring, developing and inspiring future healthcare leaders. (31st October 2017) - Rayner, E; Kurup, S; Evans, C; Tse, W; Bethune, R
Abstract : Doctors' training must provide quality improvement (QI) and leadership teaching and involvement in QI activity is already a mandatory item on the curriculum for most training schemes. Despite this, actual QI training provision remains inconsistent across different specialties and different deaneries. Dr Tse, from Health Education England(HEE) South West, led on the QI agenda for doctors in training and obtained funding for three QI Fellows, whose remits were to support learning and development in improving patient safety and patient experience. These new innovative posts were funded by HEE, and was a collaborative initiative with the South West Academic Health Science Network and Exeter University. Submitting a business case, negotiating funding and obtaining agreement from education partners for these new posts took almost two years, with the first Fellows starting in September 2016. The Fellows spent 3 days (0.6 WTE) training in their chosen specialty, 1 day (0.2 WTE) leading on a QI project and 1 day (0.2 WTE) attending Exeter University undertaking a Postgraduate Certificate in Health Services Improvement. Following intense competition, three QI Fellows drawn from the Peninsula location specialty training were appointed: Dr Kurup from General Practice, Dr Evans from Paediatrics and Dr Rayner from Obstetrics and Gynaecology. The knowledge and skills acquired through these innovative posts has enhanced our Fellows with leadership, management and innovation experience and equipped them to promote and disseminate learning in QI, ultimately improving patient safety, experience and efficiency in NHS across the South West. Creation of similar QI Fellow posts offering QI training and University accreditation funded by acute trusts could not only develop leadership and management skills, but could also attract trainees at a time when recruitment is becoming problematic in the NHS.